Detrital nutrient content and leaf species differentially affect growth and nutritional regulation of detritivores. Issue 10 (31st May 2018) - Halvorson, Halvor M.; Fuller, Chris L.; Entrekin, Sally A.; Scott, J. Thad; Evans‐White, Michelle A.
Abstract : Resource nutrient content and identity are common bottom–up controls on organismal growth and nutritional regulation. One framework to study these factors, ecological stoichiometry theory, predicts that elevated resource nitrogen (N) and phosphorus (P) contents enhance organism growth by alleviating constraints on N and P acquisition. However, the regulatory mechanisms underlying this response – including whether responses depend on resource identity – remain poorly understood. In this study, we tested roles of detrital N and P contents and identity (leaf species) in constraining growth of aquatic invertebrate detritivores. We synthesized results from seven detritivore species fed wide nutrient gradients of oak and maple detritus in the laboratory. Across detritivore taxa, we used a meta‐analytic approach quantifying effects of detrital leaf species and N and P contents on growth, consumption, and N‐ and P‐specific assimilation and growth efficiencies. Detritivore growth rates increased on higher‐N and P detritus and on oak compared to maple detritus. Notably, the mechanisms of improved growth differed between the responses to detrital nutrients versus leaf species, with the former driven by greater consumption rates despite lower assimilation efficiencies on higher‐nutrient detritus, and the latter driven by improved N and P assimilation and N growth efficiencies on oak detritus. These findings suggest animal nutrient acquisition changes flexibly in response to resource changes, altering the fate of detrital N and P throughout regulation. We affirm resource identity and nutrients as important bottom–up controls, but suggest these factors act through separate pathways to affect organism growth and thereby change detrital ecosystems under anthropogenic forest compositional change and nutrient enrichment.